Kupchik, John 2023. Azuma Old Japanese: A comparative grammar and reconstruction (Trends in Linguistics. Documentation 40). Berlin–Boston: De Gruyter Mouton. Pp. XXXIV + 522 - Majewicz, Alfred F. (Lingua Posnaniensis, 2024)
Review